PENGENDALIAN GULMA PADA KEBUN KELAPA SAWIT (Elaeis guineensis Jacq)K2IDAN KEBUNMASYARAKAT DI DESA BANGKO KIRI KECAMATANBANGKO PUSAKO KABUPATEN ROKAN HILIRPROVINSI RIAU - Rianti, Novarina; Salbiah, Desita; Khoiri, M. Amrul (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The research purpose tounderstandingthe weedcontrol anddominant weeds of palm oil (Elaeis guineensis Jacq.) plantation. The research was carried out in the village of Bangko Pusako Kabupaten Rokan Hilir from May until July 2014 with method survey, analyzed by quantitative statistics and were present in deskriptive.The sample collection by purposively sampling based on land area and age of plant. The total sample taken were 42 samples or 10 percent of 416 farmers palm oil and for the type of dominant weed done in vegetation with analysis quadrantmethod.Parameters that observed wereorigin of seed, cropping pattern distance, distance cropping, the population of plants , weeds dominant type , weed management techniques, rotation management, kind of a herbicide and dose of herbicide.The research results show farmers sample used weeds management technique with chemically and mechanically 76,2 % rate and 47.7 % farmers usedrotation management for 6 times a year, 52,38 % farmers used herbicide with active compoud  paraquat-dimethylamine, 52,3 % farmers used3l / hadose while K2I farm also do the same thing, but the management carry out twice a year. The  weeds dominant type in K2I and people farmisSpotaneum saccharum L. (shaken) 56,25 %. Keywords : weed control, dominant weed type, palm oil